2008
DOI: 10.1007/s10751-008-9712-y
|View full text |Cite
|
Sign up to set email alerts
|

Reaction and deposition of laser-evaporated iron

Abstract: Reaction of laser-evaporated iron atom was investigated by Mössbauer spectroscopy and was applied for the production of films. Iron oxide films were produced by laser-deposition of Fe metal and hematite solid onto Al substrates, and the compositions of the films changed depending on the pressure of the O 2 atmosphere and the temperature of the substrates. The spin orientations of α-Fe films deposited by three types of deposition methods were compared. The nuclear spin of iron films produced by deposition of Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Another important characteristic of laser evaporation is the generation of micrometer-sized particles, which are called 'droplets'. In previous studies [11], we investigated the effects of droplets on the deposited iron oxide films and found that droplets produce a α-Fe layer that is mixed with iron oxide layers and that the α-Fe layer did not react with the oxide in the films. In the present study, we perform PLD under conditions that suppress the production of large droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Another important characteristic of laser evaporation is the generation of micrometer-sized particles, which are called 'droplets'. In previous studies [11], we investigated the effects of droplets on the deposited iron oxide films and found that droplets produce a α-Fe layer that is mixed with iron oxide layers and that the α-Fe layer did not react with the oxide in the films. In the present study, we perform PLD under conditions that suppress the production of large droplets.…”
Section: Introductionmentioning
confidence: 99%